2023
DOI: 10.1021/acs.analchem.3c02655
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Phase Heterogeneity in Lipid Membranes Using Single-Molecule Tracking in Live Cells

Jiseong Park,
Yongdeok Ahn,
Wonhee John Lee
et al.

Abstract: In live cells, the plasma membrane is composed of lipid domains separated by hundreds of nanometers in dynamic equilibrium. Lipid phase separation regulates the trafficking and spatiotemporal organization of membrane molecules that promote signal transduction. However, visualizing domains with adequate spatiotemporal accuracy remains challenging because of their subdiffraction limit size and highly dynamic properties. Here, we present a single lipid-molecular motion analysis pipeline (lipid-MAP) for analyzing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…In addition to the previously introduced RD, phase separation is another mechanistic model used to explain the spatial patterns of biomolecules. Biocondensates created through phase separation have dynamic properties such as size variability due to fission–fusion and irregular spacing between condensates. , In contrast to phase separation, our research revealed a remarkable consistency in the spacing and size of fenestrae (Figure d–f and Figure S4). On this basis, we proposed that Turing’s RD model, which has inherent regularity due to wavelike solutions (Supplemental Note), might be more appropriate for explaining the kinetically controlled spatial organization of fenestrae.…”
Section: Rd Modeling Based On Sm Measurementsmentioning
confidence: 70%
“…In addition to the previously introduced RD, phase separation is another mechanistic model used to explain the spatial patterns of biomolecules. Biocondensates created through phase separation have dynamic properties such as size variability due to fission–fusion and irregular spacing between condensates. , In contrast to phase separation, our research revealed a remarkable consistency in the spacing and size of fenestrae (Figure d–f and Figure S4). On this basis, we proposed that Turing’s RD model, which has inherent regularity due to wavelike solutions (Supplemental Note), might be more appropriate for explaining the kinetically controlled spatial organization of fenestrae.…”
Section: Rd Modeling Based On Sm Measurementsmentioning
confidence: 70%